Peran Asisten Guru dalam Meningkatkan Kualitas Pembelajaran pada Jurusan DPIB di SMK Negeri 1 Kemlagi - Rani Wulandari; Imam Alfianto (Pusdikra Publishing, 2026)
This study examines the role of Teaching Assistants in improving the quality of learning in the Building Information Modeling and Design (BIMD) department at SMK Negeri 1 Kemlagi. Through a library research method, this study analyzes the implementation of the Teaching Assistant program, challenges faced, and its impact on learning quality. The results show that Teaching Assistants contribute significantly to enhancing learning effectiveness in BIMD classes, facilitating differentiated learning, and bridging the gap between theory and practice. The presence of Teaching Assistants also helps create a more inclusive learning environment and improves students' work readiness. However, several challenges were identified, including inadequate training, the need to improve collaboration between lead teachers and Teaching Assistants, and the risk of student dependency. To maximize the benefits of this program, more structured efforts are needed in terms of training, collaboration, evaluation, and continuous professional development for Teaching Assistants. This research highlights the importance of integrating industry perspectives into learning through the Teaching Assistant program, as well as the need to develop comprehensive evaluation mechanisms. These findings provide a foundation for future development and improvement of Teaching Assistant programs, not only at SMK Negeri 1 Kemlagi but also in other vocational education institutions in Indonesia.